Linking Scales of Life-History Variation With Population Structure in Atlantic Cod - Wright, Peter J.; Doyle, Alice; Taggart, John B.; Davie, Andrew (Frontiers in Marine Science, 2021)
It is increasingly recognised that sustainable exploitation of marine fish requires the consideration of population diversity and associated productivity. This study used a combination of genotypic screening and phenotypic traits to define the scale of population structuring in Atlantic cod inhabiting the northern North Sea (ICES Sub-division 4a) and Scottish west coast (ICES Division 6a). The genetic analysis indicated an isolation by distance pattern with an even finer scale structuring than previously reported, that persisted over a decade and between feeding and spawning seasons. Spatial variation in phenotypic traits reflected genetic variation with cod maturing later and at a larger size near the Viking Bank in 4a. The identified population structuring provides an explanation for differences in historic changes in maturation schedules and the temperature exposure recorded in previous electronic tagging studies. The study also highlights how the mismatch between stock divisions and population units is leading to a misunderstanding about stock recovery.